2011
DOI: 10.1123/jpah.8.2.157
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Psychological Adjustment in Adolescents

Abstract: Objective:To examine the association between volume and intensity of physical activity (PA) and depressive symptoms, anxiety, and body image in a large sample of adolescents in Ottawa and surrounding region.Methods:A total of 1259 (n = 746 girls and n = 513 boys) students responded to surveys on leisure time PA, depressive symptoms, anxiety, and body image.Results:A dose response effect of intensity of PA and psychological distress was observed whereby those who performed greater bouts of vigorous PA exhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 37 publications
6
22
0
4
Order By: Relevance
“…Further, recent research demonstrated a doseeresponse whereby higher intensities of physical activity were significantly correlated with reduced severity of depressive symptoms in boys aged 12e18 years but not in girls (Goldfield et al, 2011). Conversely, Katon and colleagues found no inverse associations between vigorous-intensity and depressive symptoms in youth aged 13e17 years (Katon et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Further, recent research demonstrated a doseeresponse whereby higher intensities of physical activity were significantly correlated with reduced severity of depressive symptoms in boys aged 12e18 years but not in girls (Goldfield et al, 2011). Conversely, Katon and colleagues found no inverse associations between vigorous-intensity and depressive symptoms in youth aged 13e17 years (Katon et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, research examining physical activity and depression in youth is scant with only a small number of population-based studies published to date (Larun, Nordheim, Ekeland, Hagen, & Heian, 2006). Epidemiological studies utilising child and adolescent cohorts have found inverse cross-sectional associations between leisure-time physical activity and depressive symptoms (Goldfield et al, 2011;Prasad, St-Hilaire, Wong, Peterson, & Loftin, 2009;Rothon et al, 2010) and dysthymia (Ströhle et al, 2007), and between sports participation and depressive symptoms (Desha, Ziviani, Nicholson, Martin, & Darnell, 2007). Inverse prospective associations between leisure-time physical activity and risk of depressive symptoms (Motl, Birnbaum, Kubik, & Dishman, 2004), dysthymia (Ströhle et al, 2007), and major depressive disorder (Jerstad, Boutelle, Ness, & Stice, 2010) have also been demonstrated.…”
Section: Introductionmentioning
confidence: 86%
“…The two-week time interval was considered most feasible for teachers' schedules, and considered long enough to ensure that adolescents could not remember the questionnaire in any great detail (e.g. Goldfield et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity (PA) provides fundamental health benefits for children and youth (World Health Organization [WHO], 2010), including positive effects on the musculoskeletal system and cardiovascular health (Janssen & LeBlanc, 2010), as well as self-image (Goldfield et al, 2011). Health might even be a critical partner for optimum education (Rothon et al, 2009), and studies have found associations between adolescent PA and academic performance (Fedewa & Ahn, 2011).…”
Section: > > Introductionmentioning
confidence: 99%